A multicenter, randomized trial on neuroprotection with remote ischemic per-conditioning during acute ischemic stroke: the REmote iSchemic Conditioning in acUtE BRAin INfarction study protocol. Issue 8 (October 2016) - Pico, Fernando; Rosso, Charlotte; Meseguer, Elena; Chadenat, Marie-Laure; Cattenoy, Amina; Aegerter, Philippe; Deltour, Sandrine; Yeung, Jennifer; Hosseini, Hassan; Lambert, Yves; Smadja, Didier; Samson, Yves; et al.
Rationale: Remote ischemic per-conditioning—causing transient limb ischemia to induce ischemic tolerance in other organs—reduces final infarct size in animal stroke models. Aim: To evaluate whether remote ischemic per-conditioning during acute ischemic stroke (<6 h) reduces brain infarct size at 24 h. Methods and design: This study is being performed in five French hospitals using a prospective randomized open blinded end-point design. Adults with magnetic resonance imaging confirmed ischemic stroke within 6 h of symptom onset and clinical deficit of 5–25 according to National Institutes of Health Stroke Scale will be randomized 1:1 to remote ischemic per-conditioning or control (stratified by center and intravenous fibrinolysis use). Remote ischemic per-conditioning will consist of four cycles of electronic tourniquet inflation (5 min) and deflation (5 min) to a thigh within 6 h of symptom onset. Magnetic resonance imaging is repeated 24 h after stroke onset. Sample size estimates: For a difference of 15 cm 3 in brain infarct growth between groups, 200 patients will be included for 5% significance and 80% power. Study outcomes: The primary outcome will be the difference in brain infarct growth from baseline to 24 h in the intervention versus control groups (by diffusion-weighted image magnetic resonance imaging). Secondary outcomes include: National Institutes of Health Stroke Scale score absolute difference between baseline and 24 h, three-month modified Rankin score and daily living activities, mortality, and tolerance and side effects of remote ischemic per-conditioning. Discussion: The only remote ischemic per-conditioning trial in humans with stroke did not show remote ischemic per-conditioning to be effective. REmote iSchemic Conditioning in acUtE BRAin INfarction, which has important design differences, should provide more information on the use of this intervention in patients with acute ischemic stroke.